Knowledge of cardiovascular disease in South African HIV-positive surgical patients – A pilot survey - Dellar, Rachael; Madiba, Thandinkosi; Moodley, Yoshan (SA Heart Journal, 2019)
Background: Medical and surgical HIV-positive patients are at risk of cardiovascular disease (CVD). Surgical patients are admitted to hospital for a few days around the time of their surgeries, allowing sufficient opportunity for health promotion interventions. Health promotion could improve CVD knowledge and encourage lifelong healthy behaviours. However, this approach requires that baseline CVD knowledge first be established. This study sought to determine the knowledge of CVD in HIV-positive South African (SA) surgical patients. Methods: This was a prospective pilot survey of HIVpositive surgical patients who attended a tertiary hospital in Durban, South Africa, between 1 October 2016 and 31 March 2017. Patients completed 2 questionnaires: (1) a demographic characteristics questionnaire, and (2) a CVD knowledge questionnaire (identifying risk factors and signs/symptoms of myocardial infarction and stroke). All data were analysed using descriptive statistical methods. Results: The study sample consisted of 39 HIV-positive surgical patients. Correct responses for the items on the CVD knowledge questionnaire ranged between 0.0% and 61.5% for risk factors, and between 0.0% and 89.7% for signs/symptoms. Conclusion: Knowledge of CVD risk factors and signs/ symptoms in this study was less than desirable. Levels of CVD knowledge are likely a function of educational attainment.